Commissioning an Elekta Versa HD linear accelerator. Issue 7 (July 2016) - Gillespie, Sean; Woulfe, Peter
Abstract : The Versa HD not only brought kV image guided radiotherapy to our department, it also enabled the department to offer VMAT and high dose-rate (FFF) treatments. This study describes the dosimetric aspects of commissioning performed on an Elekta Versa HD for both flattened & FFF photon modes. Photon PDD & profiles agreed well with expected values as per the acceptance testing protocol/literature. The PDDs of 6 MV FFF and 10 MV FFF beams show deeper dmax and steeper falloff with depth than the corresponding flattened beams. While flatness values of 6 MV FFF and 10 MV FFF profiles were expectedly higher than the corresponding flattened beams while the symmetry values were remained similar. Photon data was modelled in Pinnacle TPS. Verification consisted of point dose measurements, profile analysis using PTW's 2D Array/Verisoft software and a phantom study (solid, air and lung inserts). Two interdepartmental independent dose audits were carried out along with an alanine postal audit (NPL) and MD Anderson Prostate & Head SRS audits for extended verification of the pinnacle models. 6MV VMAT planning was investigated using Pinnacle's Smartarc solution which yielded at least equivalent if not more favourable results whilst reducing treatment time. Patient Specific VMAT QA of treatment plans were carried out with PTW OCTAVIUS 4D/Verisoft Software in conjunction with Radcalc Monitor Unit Calculation Software. All planning/delivery combinations showed good agreement with >95% pixels passing γ  < 1 at 3%/3mm. Similar results in terms of planning/verification agreement were obtained with 6MV FFF VMAT plans.